Diffraction Losses in a Stack of Diamond X-Ray Lenses - Nataliya Klimova; Anatoly Snigirev (Photonics)
Compound refractive lenses, crafted from single-crystal materials like diamond and silicon, are increasingly favored, particularly in cutting-edge facilities, such as free electron lasers and fourth-generation synchrotrons. These lenses are prized for their low parasitic scattering and resistance to significant radiation doses over extended periods. However, they do encounter a notable drawback known as the “glitch effect”, wherein undesired diffraction can occur across various X-ray energies. This phenomenon leads to a decrease in transmitted intensity, impacting experiments, particularly in spectroscopy. Typically, a series of lenses is employed to achieve optimal beam parameters, and each lens has its own spectrum of glitches. This paper presents experimentally measured glitches in stacks of 1, 4, 8, and 16 diamond compound refractive lenses, elucidating the theory behind glitch formation and offering strategies to predict and mitigate glitches in diverse focusing systems employing lenses made from single-crystal materials.